Adoption of Environment-Friendly Cars: Direct vis-à-vis Mediated Effects of Government Incentives and Consumers' Environmental Concern across Global Car Markets. Issue 4 (8th August 2018) - Chu, Wujin; Baumann, Chris; Hamin, Hamin; Hoadley, Susan
ABSTRACT: This study explores the impact of consumers' concern for the environment, government incentives, and consumers' environmental image on the adoption of environment-friendly cars (EFCs). A total of 2, 400 consumers across five key car markets (China, Germany, Japan, South Korea, USA) were sampled. Structural equation modelling was conducted, followed by ANOVA and UNIANOVA. In four of the five markets, environmental concern is key in the adoption of EFCs, whereas government incentives appear generally ineffective. China is contrastive in that government incentives, rather than environmental concerns, are a key factor. Environmental image only (significantly) mediates the adoption of EFCs in China. Examination of the interaction between environmental image and the adoption of EFCs indicates that environmental image has different impacts in different markets.